Implementasi Moderasi Beragama pada Program Qiroatul Kutub, Tadarus Al-Qur’an, dan Kegiatan Pondok Ramadhan di MAN 3 Kediri - Laily Fauziyah; Labib Mustofa; Zida Amaliya Suseno; Qulya Alvin Jana Nugraheni (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2024)
Abstract: This Student Work Lecture Activities (KKM) article discusses the implementation of the Pondok Ramadhan program which was carried out at MAN 3 Kediri during the holy month of Ramadhan. This program aims to improve the quality of participants' faith and knowledge through various religious activities such as qiroatul pole, tadarus Al-Qur'an, and sharing takjil. Book recitation activities are focused on deepening religious knowledge through studying the yellow book, which provides a deeper understanding of Islamic teachings. Tadarus Al-Qur'an is carried out alternately in each class with the aim of improving Al-Qur'an reading skills and strengthening togetherness between students. The takjil sharing program is a real form of social care, which distributes food for breaking the fast to local people who need it. The results of this activity showed a significant increase in participants' understanding of religious teachings, ability to read the Koran, and sense of social concern. This activity also strengthens relationships between participants and the community, and provides valuable experience in terms of service and cooperation. Thus, the Pondok Ramadhan program succeeded in achieving its objectives and made a positive contribution to the spiritual and social development of participants and the surrounding community.